The role of Platelet-Rich Plasma (PRP) in burn wound healing: a literature-review - Ni Kadek Parswa Diah Pradnyandari; Ratna Rayeni Natasha (Intisari Sains Medis, 2022)
Burn-related morbidity and mortality are usually caused by secondary infection and long healing time. In these circumstances, the use of products that can accelerate and enhance the wound healing process is urgently needed. One breakthrough in wound healing therapy is platelet-rich plasma (PRP). Platelet-rich plasma is autologous plasma with a platelet concentration above the normal value. This study is a literature review aiming to describe the role of PRP in burn wound healing. PRP has various mechanisms in burn wound healing, such as increasing hemostasis, releasing growth factors, reepithelialization, inducing fibroblast proliferation in the extracellular matrix, and promoting angiogenesis which increases the rate of wound healing. In addition, it also has an antimicrobials effect. Previous studies have been done in animal models and humans to prove the efficacy of PRP in burn wound healing. Most studies have revealed that PRP can accelerate wound healing time and increase the quality of wound healing. So, using PRP in burns can be very useful for patients to reduce burn morbidity and mortality.